All for Beauty Makeup and Hairdressing in Hollywood's Studio Era. - McLean, Adrienne L. (Techniques of the Moving Image Ser., 2022)
Ever wonder why so many stars and featured players, male or female, in movies of Hollywood's "Golden Age" look like they just stepped out of a beauty parlor even if the story places them in a jungle, a hospital bed, or the ancient past? All for Beauty examines how and why makeup and hairdressing evolved as crafts designed partly to maintain the white flawlessness of men and women as a value in the studio era. The book pays particular attention to the labor force, exploring the power and influence of cosmetics inventor and manufacturer Max Factor and the Westmore dynasty of makeup artists but also the contributions of others, many of them women, whose names are far less known. At the end of the complex, exciting, and at times dismaying chronicle, it is likely that readers will never again watch Hollywood films without thinking about the roles of makeup and hairdressing in creating both fictional characters and stars as emblems of an idealized and undeniably mesmerizing visual perfection.